2019
DOI: 10.3390/coatings9020107
|View full text |Cite
|
Sign up to set email alerts
|

Annealing-Driven Microstructural Evolution and Its Effects on the Surface and Nanomechanical Properties of Cu-Doped NiO Thin Films

Abstract: The effects of annealing temperature on the structural, surface morphological and nanomechanical properties of Cu-doped (Cu-10 at %) NiO thin films grown on glass substrates by radio-frequency magnetron sputtering are investigated in this study. The X-ray diffraction (XRD) results indicated that the as-deposited Cu-doped NiO (CNO) thin films predominantly consisted of highly defective (200)-oriented grains, as revealed by the broadened diffraction peaks. Progressively increasing the annealing temperature from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It has been reported that the crystallinity of Bi2Se3 thin films deposited on InP(111) substrate was better than those deposited on Al2O3 and Si substrates [35]. In general, better film crystallinity often results in superior nanomechanical properties [43,44]. Therefore, compared with those reported in [14], the larger values of hardness and Young's modulus of the present Bi2Se3 thin films could be attributed to their better crystallinity.…”
Section: Nanomechanical Propertiesmentioning
confidence: 67%
“…It has been reported that the crystallinity of Bi2Se3 thin films deposited on InP(111) substrate was better than those deposited on Al2O3 and Si substrates [35]. In general, better film crystallinity often results in superior nanomechanical properties [43,44]. Therefore, compared with those reported in [14], the larger values of hardness and Young's modulus of the present Bi2Se3 thin films could be attributed to their better crystallinity.…”
Section: Nanomechanical Propertiesmentioning
confidence: 67%
“…Nanoindentation has become a widely used technique for extracting prominent mechanical properties, namely the hardness and elastic modulus, as well as to unveil the dislocation-mediated plastic deformation and the fracture behaviors of a wide variety of nanostructures [9][10][11] and oxide thin films [12][13][14]. The relationship between the microstructure and nanomechanical characterizations of the Bi 2 Te 3 /Al 2 O 3 (001) thin films deposited at the various T S by means of PLD is systematically investigated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…For practical applications, since the manufacturing and packaging processes are inevitably involving contact loading, it is thus necessary to fully recognize the mechanical characteristics of Co thin films, especially in the nanoscale regime. To this respect, nanoindentation stands out as one of the most efficient tools for obtaining the basic mechanical characteristics, such as the hardness and elastic modulus, at small length scales of various thin films [7][8][9][10] or micro/nano-sized materials [11][12][13][14][15] owing to its advantages of high sensitivity, good resolution and easy operation. In addition, it has been widely recognized that the loading and unloading segments of the nanoindentation load-displacement curves often reflect rich information about the dominant deformation mechanism prevailing in the materials under investigation.…”
Section: Introductionmentioning
confidence: 99%